Electrospun Tissue Engineered Vascular Grafts - Hülk, Vincent Martin (Department of Human Biology, 2024)
ePTFE and Dacron vascular grafts are successful in large diameter applications but provide poor outcomes in small diameter (<6 mm) applications. Occlusion, poor cell ingrowth and a mismatch of compliance compared to the native vessel, cause failure to the current synthetic grafts. Spontaneous transmural endothelialisation can be enhanced in non-degradable scaffolds with heparin-mediated growth factor delivery via heparin surface modification, as well as induce an anti-thrombotic lumen. Electrospinning of vascular grafts offer a means to mimic the natural extracellular matrix (ECM) with improved porosity and pore for increased cell ingrowth, incorporation of drugs for sustained release, and tailoring mechanical properties match that of the native vessel. This study aims to produce a small diameter biodegradable vascular graft with sufficient porosity/pore size and incorporated heparin as an angiogenic/anti-thrombotic agent. DegraPol® (DP30), a degradable polyurethane was dissolved in different ratios of chloroform/HFIP (24%w/w) and electrospun at 30%, 40%, and 50% rH to obtain a small diameter vascular graft with improved porosity/pore size and mechanical properties. The sodium salt of heparin (HepNa+ ) was modified to heparin tributylamine (HepTBA) to ensure the solubility in organic solvents and incorporated into the electrospinning solution at 3% and 5% wt/wt (w HepTBA/w polymer). The grafts were analysed for morphological (fibre diameter, porosity/pore size, fibre alignment) and mechanical (hoop stress, strain, burst pressure, compliance) properties. After in vitro elution and degradation studies, grafts (DP30 and DP30+3%HepTBA) were evaluated in an in vivo pilot study using a rat infrarenal aortic interposition model (28 days). Relative humidity did not significantly influence the scaffold morphology or the mechanical properties, for solvent systems used. However, the addition of HFIP to the solution had on average a 2.9-fold decrease in the circumferential UTS and strain from 0.63±0.16 MPa and 90±16%, respectively. The grafts showed theoretical compliance in the physiological range of 6-8%/100mmHg and showed a significant amount of drug release in the first 5 days and a cumulative release of 62% and 36% (respectively) by day 28. The DP30 and DP30+3%HepTBA grafts lost 46% (P> 0.5) and 50% (P< 0.01) of its circumferential UTS respectively, whereas the loss in maximum strain for the same groups was 66% (P< 0.0001) and 76% (P< 0.01). A porosity of 64.5±2.7% and 54.9±2.2% (P< 0.01) was achieved for the DP30 and DP30+3%HepTBA with 52% and 29% of the pore sizes larger than 10 µm. The in vivo pilot study showed patent grafts with tissue ingrowth and endothelium on the lumen for DP30 as well as the DP30+3%HepTBA group. The DP30 grafts show promise for the replacement of small diameter vessels. Heparin-eluting grafts will be further evaluated in long-term isolated loop models to determine their capacity for spontaneous transmural endothelialisation.